A comparison of anterior cervical discectomy and fusion combined with cervical disc arthroplasty and cervical disc arthroplasty for the treatment of skip-level cervical degenerative disc disease: A retrospective study. Issue 41 (October 2017) - Wu, Ting-kui; Wang, Bei-yu; Deng, Ming-dan; Hong, Ying; Rong, Xin; Chen, Hua; Meng, Yang; Liu, Hao
Abstract : Abstract: Anterior cervical discectomy and fusion (ACDF) has been widely performed for the treatment of multilevel cervical degenerative disc disease (CDDD). In recent decades, cervical disc arthroplasty (CDA) and hybrid surgery (HS) have been developed to overcome the shortcomings of ACDF. Controversy still remains with regard to the optimal surgical procedure for skip-level CDDD. A total of 55 patients who received surgical treatment for skip-level CDDD in our department were reviewed. The patients were divided into the HS group (n = 29) and the CDA group (n = 26). The collected data included Japanese Orthopedic Association (JOA), Neck Disability Index (NDI), and Visual Analog Scale (VAS) scores, and cervical lordosis (CL), range of motion (ROM), and intervertebral disc height (IDH). Radiological changes at the intermediate segment (IS) were also collected. All data were collected preoperatively and at routine postoperative intervals of 1 week and 3, 6, and 12 months and at the last follow-up period. Compared with preoperative values, mean JOA, NDI, and VAS scores significantly improved after surgery in both the HS and CDA groups ( P < .05). However, there were no significant differences between the groups ( P > .05). The HS group had better CL recovery than the CDA group after surgery ( P < .05). There was no significant difference in the ROM of C2–C7 between the 2 groups ( P > .05). A significant difference in the ROM of the IS was found at the last follow-up between the 2 groups ( P < .05). At the last-follow-up, 4 discs (14.29%) in the CDA group and 6 discs (19.36%) in the HS group had adjacent segment degeneration (ASD) without symptoms. Both HS and CDA might be considered safe and effective surgical strategies for the treatment of skip-level CDDD. Although the clinical outcomes were similar in the 2 groups, CDA altered the ROM of the IS to a lesser degree.